(untitled) (Academia Science Repository, 2023)
In this article, the topical issue of today is the formation of situational immunity in adolescence. It is stated that the formation of ideological immunity is the most important task of society and is directly related to the national feelings, goals and aspirations of young people, as well as to the spiritual and educational and spiritual and ethical level.